Behavioural responses of Australian freshwater crayfish (Cherax tenuimanus and Cherax albidus) to water-borne odours - Height, Shaun Gareth (Curtin University, 2008)
Interactions between non-native yabbies (Cherax albidus) and indigenous marron (Cherax tenuimanus) in the south-west of Western Australia are not well understood. While there is abundant evidence to suggest that invasive freshwater crayfish are detrimental to native species, the nature and degree of impact on marron populations by exotic yabbies remains unclear. Researchers have hypothesized that invasive species make faster and more appropriate use of information about their environment than native species. This greater behavioural plasticity can result in displacement of indigenous species, successful colonisation by invaders, and subsequent disturbance to natural ecosystems and representative biodiversity.The research presented in this thesis examines the behavioural responses of an indigenous crayfish (C. tenuimanus) and an invasive crayfish (C. albidus) to waterborne odours derived from food, alarm sources and finfish predators. This study was undertaken to assist in the understanding of predatory and competitive interactions between indigenous and non-indigenous crayfish and fish predators, with particular relevance to Western Australia. Predation and competition are major forces influencing community structure in ecosystems; therefore knowledge of competitive and predatory interactions will be of benefit when considering future translocation policies.Behavioural trials were conducted in two culture systems (54 L aquaria and a 70,000 L mesocosm), where marron and yabbies were exposed to a range of water-borne odours from finfish predators (silver perch and Murray cod), with and without competition from conspecific and heterospecific crayfish. A number of variables likely to influence crayfish behaviour were investigated: strength of chemical odour; crayfish size, gender, diurnal and nocturnal activity patterns; predator size; prior-residence; suitable habitat/shelter; and feed availability.A key innovation in this research was the high replication in the aquarium-based observation trials using a Latin Cube design, which resulted in greater statistical strength and lower variability. More importantly, this research deviated from the tradition of exclusively using the ‘individual crayfish’ approach for odour-detection experiments and tested these results in a 70,000 L communal observation tank. This was an important development in crayfish behavioural experimentation, particularly as several key findings from the individual crayfish approach were confirmed in a multi-species environment.Results from this study supported the hypothesis that invasive crayfish species make more appropriate use of a wider range of information about their environment than native crayfish species. Yabbies were found to possess behavioural characteristics not present in marron, such as clearer behavioural modifications to food and heterospecific odour, and cautionary behaviour in the presence of odour from a finfish predator. During simulated daylight conditions, marron displayed behaviours conducive to predation that were not present in yabbies, including less time spent in shelter and more time spent in locomotory activity. However, during specialised night-time observational studies developed during this research, these differences were not evident. This would not seem to be an unusual result, given that crayfish naturally forage at night and become more active; however, it may have important implications for future behavioural studies of crayfish, indicating a bias associated with day-time approaches. Crayfish size also played a role in behavioural modifications to water-borne odours. Larger marron displayed clearer changes in behaviour and were more responsive to heterospecific alarm odour than juveniles. Furthermore, juveniles of both species were more active than adults and sub-adults.The expansion of the yabby population into Western Australian habitats occupied by marron has been facilitated through translocation for aquaculture, and biological characteristics of the species, some of which are typical of other invasive crayfish species including: tolerance of a variety of conditions; rapid growth; early sexual maturity; burrowing to escape drought and predation; capable of multiple spawns in a growth season; and aggressiveness. Another characteristic of invasive crayfish species also shared by yabbies, as supported by the results of this study, is high behavioural plasticity.Although marron do not share the same level of behavioural plasticity found in yabbies, their larger body size increases their success in competitive interactions. The comparatively smaller body size of yabbies may be the major factor limiting their population expansion in the presence of marron, especially in water-bodies where shelter is a limited resource.Marron are an important endemic species in Western Australia, but their conservation is threatened by competition and predation from exotic species. The research presented in this thesis indicates that invasive yabbies are more receptive to chemical stimuli and better equipped to respond to predation risk than marron. This information will be of benefit when considering future translocation policy in Western Australia and highlights the need for a cautious approach to species introductions.